Historical assessment and future sustainability challenges of Egyptian water resources management. (1st August 2020) - Luo, Pingping; Sun, Yutong; Wang, Shuangtao; Wang, Simeng; Lyu, Jiqiang; Zhou, Meimei; Nakagami, Kenichi; Takara, Kaoru; Nover, Daniel
Abstract: The sustainable and efficient use of water is of vital importance, and the uneven distribution of water in the world means that it is especially important for water-scarce countries. Egypt is an arid country with an ancient civilization and a long history that was and remains dependent on the trans-boundary water resources of the Nile River. Historically complicated, water resource management in Egypt is becoming more so in the face of urbanization and population growth. We present a comprehensive overview of the water management policies in Egypt to identify current trends and conditions. Under the population growth, the available water use for all the governorates is shown the decreasing trend in 2025 compared with that in 2012, but only the available water use in governorate of Red Sea is shown the increasing trend with 0.022 BCM(Billion Cubic Meter) in 2025 than that in 2012. Historical assessment of water resources management allows for the reconsideration of present conditions and planning for future sustainability challenges. Egypt's present national plan reflects a transition from traditional approaches to demand management. At the same time, responsibility for water resources management has shifted from the local to the national level. Sustainability of water resource systems will require consideration of the negative impacts of population growth as well as urban development and further coordination of national and local priorities. This study explores the changes and reforms of water policies in Egypt, as well as challenges and implications for sustainable water governance and management. Graphical abstract: Image 1 Highlights: Reviewing Egypt's water management history helps address contemporary stresses. Egypt is moving from traditional water management to demand management. Oversite of water resources has shifted from local to national level. Climate change, population growth and urban development challenge sustainability. Addressing challenges requires national and local level coordination.